2016
DOI: 10.1371/journal.pone.0155099
|View full text |Cite
|
Sign up to set email alerts
|

Six Tissue Transcriptomics Reveals Specific Immune Suppression in Spleen by Dietary Polyunsaturated Fatty Acids

Abstract: Dietary polyunsaturated fatty acids (PUFA) are suggested to modulate immune function, but the effects of dietary fatty acids composition on gene expression patterns in immune organs have not been fully characterized. In the current study we investigated how dietary fatty acids composition affects the total transcriptome profile, and especially, immune related genes in two immune organs, spleen (SPL) and bone marrow cells (BMC). Four tissues with metabolic function, skeletal muscle (SKM), white adipose tissue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 49 publications
(68 reference statements)
6
24
0
Order By: Relevance
“…This pattern is in accordance with the findings of our previous microarray analysis performed in the spleen, bone marrow, skeletal muscle, white adipose tissue, and brown adipose tissue from mice fed LFD, HFD-S, or HFD-P (20). In such an analysis, bone marrow and skeletal muscle were relatively unchanged by the diets, whereas both white and brown adipose tissues were similarly affected by HFD-S and HFD-P.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This pattern is in accordance with the findings of our previous microarray analysis performed in the spleen, bone marrow, skeletal muscle, white adipose tissue, and brown adipose tissue from mice fed LFD, HFD-S, or HFD-P (20). In such an analysis, bone marrow and skeletal muscle were relatively unchanged by the diets, whereas both white and brown adipose tissues were similarly affected by HFD-S and HFD-P.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously reported that mice fed HFD-S have an increased liver size compared with mice fed LFD and HFD-P after 8 weeks of diet (20). However, after 4 weeks of diet, the size of the liver was not altered by either HFD-S or HFD-P ( Fig.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, feeding a diet rich in n-3 FA to fattening pigs led to a suppression of pro-inflammatory markers and an increased gene expression of detoxifying enzymes in the spleen (Taranu et al, 2014). Studies in mice confirmed that the spleen is one of the target organs for the anti-inflammatory effects of n-3 FA (Soni et al, 2017;Svahn et al, 2016). In the lung, feeding a diet rich in n-3 FA to pigs attenuated the response to endotoxin injection compared to groups fed diets rich in n-6 FA (Murray et al, 1993).…”
Section: Differences In Partitioning Of N-3 and N-6 Fas From The Oil mentioning
confidence: 97%